Detection of shiga toxin-producing Escherichia coli (STEC) serogroups other than the Top-7 STEC, isolated from cattle feces, by Multiplex PCR assays - Pedrow, Alexis; Ludwig, Justin; Shi, Xiaorong; Bai, Jianfa; Nagaraja, T.G. (My University, 2017)
Purpose: Shiga toxin producing Escherichia coli (STEC) are major foodborne pathogens. Among STEC, seven serogroups, O26, O45, O103, O111, O121, O145, and O157, called top-7 STEC, cause a majority of foodborne STEC infections in humans. These STEC reside in the hindgut of cattle and are shed in the feces, which is the major cause of contamination of beef, produce, and water sources. Cattle harbor several other serogroups (n=113) of STEC, however, not all have been reported to cause human illness. We have developed and validated (n=11) multiplex PCR assays to detect (n=113) non-top-7 STEC serogroups. Our objective was to identify the serogroups of STEC, isolated from cattle feces, that were not positive for the top-7 STEC by multiplex PCR assays targeting specific genes for each serogroup. Methods: Two hundred forty-one strains, isolated from pen-floor samples, collected from eight feedlots in the central U.S. were included in the study. The fecal samples were collected over a 12 week period from June 2014 to August 2014. All 241 strains of E. coli were positive for the stx1 (Shiga toxin 1), stx2 (Shiga toxin 2), or both, and/or the eae (intimin) genes, but negative for the top-7 STEC serogroups. Multiplex PCR assays developed and validated with known serogroups, that target the wzx and wzy gene in the O-antigen of specific serogroups for STEC were used for the identification of the serogroups. Results: Of the 241 strains from the eight feedlots, 203 strains (84.2%) belonged to 19 serogroups and 38 (15.8%) are unidentified. The 19 serogroups included O168, O109, O131, O2, O104, O8, O74, O171, O136, O178, O102, O98, O175, O118, O113, O96, O76, O35, and O20. (Table 1) Significance: Cattle are reservoirs for many STEC serogroups, including those that are not a part of the top-7. This illustrates that cattle harbor diverse serogroups of STEC in the gut and shed them in the feces. The four most predominant serogroups for the eight feedlots were: O168 (72/241 29.9%), O109 (40/241 16.6%), O131 (28/241 11.6%), and O2 (20/241 8.3%). Serogroup O168 was isolated from post-weaned pigs with diarrhea (Ho et. Al. 2013). Serogroup O109 has been isolated from samples of cheese made with raw milk in France and poses a potential health risk in human consumers (Vernozy-Roznad et. Al. 2005). Serogroup O131 was isolated from fecal samples of chickens with diarrhea (Wani et. Al. 2004). Serogroups O2 has been isolated from humans with diarrhea and urinary tract infections (Rizvi et. Al. 2003). The dominance of a few serogroups of STEC that do not belong to the top-7 STEC in cattle feces suggests potential risk to cause illness in humans.
Keywords: Fall 2017